Phytosociological survey of weed plants and their pasture control - Luz do Carmo Silva, Gidean; Toniolo Farias, Henrique; de Oliveira Neto, Joaquim; Vargas Borges, Elizene; Wenderson Ribeiro Coutinho, Pablo (Scientia Agraria Paranaensis, 2021)
Weeds damage economically interesting crop development, resulting in potential production loss of such crop. Thus, this study had de objective of surveying weeds’ phytosociology in Brachiaria brizantha (cv. Marandu) pasture and of evaluating the effectiveness of herbicides in mixtures on weeds control. The field studied has been using B. brizantha pasture for more than 10 years, divided in 4 areas with 1 ha each. After the first weeds harvest and identification, a mixture of Aminopyralid (50 g L-1) + Picloram (100 g L-1) + Triclopyr (150 g L-1) 1 L ha-1 + 1.5 L ha-1 of 2,4-D (2.5 L ha-1), Aminopyralid (50 g L-1) + Picloram (100 g L-1) + Triclopyr (150 g L -1) 2.0 L ha-1 + 1.5 L ha-1 of 2,4-D (3.5 L ha-1), Aminopyralid (50 g L-1) + Picloram (100 g L-1) + Triclopyr (100 g L-1) 1 L ha-1 + 1.0 L ha-1 of 2,4-D (2 L ha-1). After the harvests, the samples were identified and the following statistics were calculated — absolute frequency, relative frequency, absolute density, relative density, absolute abundance, relative abundance, and importance value index. The obtained phytosociological survey in pasture planting presented five families — Fabaceae, Malvaceae, Asteraceae, Euphorbiaceae, and Solanaceae —, and using Aminopyralid (50 g L-1) + Picloram (100 g L-1) + Triclopyr (100 g L-1), adding up to a mixture of 1.0 L ha-1, mixed with 1.0 L ha-1 of 2,4-D, was effective in the control of weeds in the pasture area.